Adaptive Probability Estimation Techniques for Context Adaptive Arithmetic Coding - Krishnan, Madhu P; Zhao, Xin; Liu, Shan (IEEE International Symposium on Circuits and Systems proceedings, 2023)
Context-adaptive arithmetic coding is an essential entropy coding scheme used in all modern video codecs. An arithmetic coder with binary symbol size is used by video codecs like H.264/AVC, HEVC and VVC while AV1 utilizes an arithmetic coder with syntax adaptive M-ary symbols. Recently, the Alliance for Open Media (AOMedia) has initiated exploration activities towards next-generation video coding tools beyond AV1. In this regard, improvements on probability estimation techniques for the context-adaptive M-ary arithmetic coder in AV1, are explored in this paper. The proposed improvements are applied and tested on top of the reference implementation of the exploratory codec beyond AV1, known as AVM (AOMedia Video Model). Experimental results show that, compared to AVM, the proposed method achieves an average 0.27%, 0.34% and 0.32% overall BD-rate coding gains for All Intra (AI), Random Access (RA) and Low Delay (LD) coding configurations for a wide range of video content.